Comparison of the Efficacy of S-1 Plus Oxaliplatin or Capecitabine Plus Oxaliplatin for Six and Eight Chemotherapy Cycles as Adjuvant Chemotherapy in Patients With Stage II-III Gastric Cancer After D2 Resection - Yu, Yuanyuan; Zhang, Zicheng; Meng, Qianhao; Ma, Yue; Fan, Xiaona; Sun, Jie; Wang, Guangyu (Frontiers in Oncology, 2021)
Abstract Objective To compare the efficacy of adjuvant chemotherapy with six or eight cycles of SOX or XELOX after D2 resection of GC. Design and participants We collected 470 cases of patients with TNM stage II and III GC who underwent D2 gastrectomy in the Harbin Medical University Cancer Hospital from January 2007 to December 2017 and had received six or eight cycles of SOX or XELOX regimen. This study was designed to evaluate prognosis of patients receiving six or eight cycles of SOX or XELOX chemotherapy and identify the appropriate number of chemotherapy cycles. Results Among the 470 study participants [340 (72.3%) males; median age, 50 years (range, 24–76 years)], 355 and 115 received XELOX and SOX regimen chemotherapy, respectively. The number of 152 patients included in this study who received 6 and 8 cycles of chemotherapy in stage II and stage III without considering chemotherapy regimens were 125 and 27, and the median DFS were, respectively, 14.9 months and 26.8 months (P = 0.08), the median OS were, respectively, 30.2 months and 30.8 months (P = 0.5), the difference was not statistically significant. Comprehensive analysis of XELOX and SOX group DFS (P = 0.29) and OS (P = 0.61) showed no significant difference. The total number of stage III GC patients who received six and eight cycles of chemotherapy were 92 and 19, respectively. The median DFS of patients who received six and eight cycles of chemotherapy was 14.6 and 23.2 months (P = 0.3), respectively. The median OS in patients who received six and eight cycles of chemotherapy was 26 and 30.6 months (P = 0.9), respectively. Comprehensive analysis of DFS (P=0.73) and OS (P=0.6) shows no difference between the XELOX group SOX groups. Subgroup analysis revealed significant differences in the gender (P = 0.05) and histological classification (P < 0.05) distribution. Conclusion: Regardless of the XELOX regimen or the SOX regimen, similar survival benefits are observed in patients receiving six or eight chemotherapy cycles irrespective of the regimen used. The XELOX and SOX regimens are well tolerated in patients undergoing D2 resection of GC.